2016
DOI: 10.3390/ijms17060836
|View full text |Cite
|
Sign up to set email alerts
|

Follicle Loss and Apoptosis in Cyclophosphamide-Treated Mice: What’s the Matter?

Abstract: With increasing numbers of young female cancer survivors following chemotherapy, chemotherapy-induced fertility loss must be considered. Menstrual disorder and infertility are of particular concern in female cancer patients. We showed that treatment with the alkylating agent cyclophosphamide (CTX) could cause severe primordial follicle loss and growing follicle apoptosis, resulting in loss of ovarian reserve. SPF C57BL/6 female mice were treated with a single dose of 120 mg/kg of CTX or saline as a control, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 20 publications
5
46
3
Order By: Relevance
“…Our results are in accordance with the burnout effect because we showed, using Western blot analyses of whole ovaries, an increase in the phosphorylation of key proteins of the PI3K pathway in mice treated with Cy. Others have also confirmed this mechanism, with Cy or with other chemotherapeutic agents (29)(30)(31).…”
Section: Discussionmentioning
confidence: 81%
“…Our results are in accordance with the burnout effect because we showed, using Western blot analyses of whole ovaries, an increase in the phosphorylation of key proteins of the PI3K pathway in mice treated with Cy. Others have also confirmed this mechanism, with Cy or with other chemotherapeutic agents (29)(30)(31).…”
Section: Discussionmentioning
confidence: 81%
“…Chemotherapy and radiotherapy[ 55 ] lead to ovarian damage and can cause POF. Cyclophosphamide[ 56 ] induces the hyperactivation of the phosphatidylinositol-3-kinase/protein kinase B/the mammalian target of rapamycin signaling pathway in ovaries, which leads to primordial follicle loss and increased follicle apoptosis. Although firm evidence is lacking, dioxin[ 54 ] exposure may also influence the ovarian reserve, and cigarette smoke[ 57 ] induces dysfunction of mitochondrial repair mechanisms, leading to autophagy-mediated follicle death.…”
Section: R Elationship Between O Varian mentioning
confidence: 99%
“…[7][8][9] Previous studies have demonstrated follicular decline after cyclophosphamide treatment, and have indicated that apoptotic changes in granulosa and theca cells are the mechanism that leads to follicle loss. 10 In previous reports, testosterone was shown to be essential for normal follicular development; it enhances follicular recruitment, 11 promotes follicular growth and development, 12 increases the insulin-like growth factor 1 expression in the primate ovary to induce follicular development, 13 and increases follicular sensitivity to follicle-stimulating hormone via the androgen receptor. 14,15 However, high concentrations of testosterone inhibit follicle development through the regulation of the folliclestimulating hormone signaling pathway.…”
Section: Introductionmentioning
confidence: 98%